Physiological and Biomechanical Responses of Highly Trained Distance Runners to Lower-Body Positive Pressure Treadmill Running - Kyle R. Barnes; Jessica N. Janecke (SpringerOpen, 2017)
Abstract Background As a way to train at faster running speeds, add training volume, prevent injury, or rehabilitate after an injury, lower-body positive pressure treadmills (LBPPT) have become increasingly commonplace among athletes. However, there are conflicting evidence and a paucity of data describing the physiological and biomechanical responses to LBPPT running in highly trained or elite caliber runners at the running speeds they habitually train at, which are considerably faster than those of recreational runners. Furthermore, data is lacking regarding female runners' responses to LBPPT running. Therefore, this study was designed to evaluate the physiological and biomechanical responses to LBPPT running in highly trained male and female distance runners. Methods Fifteen highly trained distance runners (seven male; eight female) completed a single running test composed of 4 × 9-min interval series at fixed percentages of body weight ranging from 0 to 30% body weight support (BWS) in 10% increments on LBPPT. The first interval was always conducted at 0% BWS; thereafter, intervals at 10, 20, and 30% BWS were conducted in random order. Each interval consisted of three stages of 3 min each, at velocities of 14.5, 16.1, and 17.7 km·h−1 for men and 12.9, 14.5, and 16.1 km·h−1 for women. Expired gases, ventilation, breathing frequency, heart rate (HR), rating of perceived exertion (RPE), and stride characteristics were measured during each running speed and BWS. Results Male and female runners had similar physiological and biomechanical responses to running on LBPPT. Increasing BWS increased stride length (p < 0.02) and flight duration (p < 0.01) and decreased stride rate (p < 0.01) and contact time (p < 0.01) in small-large magnitudes. There was a large attenuation of oxygen consumption (VO2) relative to BWS (p < 0.001), while there were trivial-moderate reductions in respiratory exchange ratio, minute ventilation, and respiratory frequency (p > 0.05), and small-large effects on HR and RPE (p < 0.01). There were trivial-small differences in VE, respiratory frequency, HR, and RPE for a given VO2 across various BWS (p > 0.05). Conclusions The results indicate the male and female distance runners have similar physiological and biomechanical responses to LBPPT running. Overall, the biomechanical changes during LBPPT running all contributed to less metabolic cost and corresponding physiological changes.